Density dependent regulation of inflammatory responses in macrophages - Vaughan-Jackson, Alun; Stodolak, Szymon; Ebrahimi, Kourosh H.; Johnson, Errin; Reardon, Paul K.; Dupont, Maeva; Zhang, Shengpan; McCullagh, James S. O.; James, William S. (Frontiers in Immunology, 2022)
Macrophage distribution density is tightly regulated within the body, yet the importance of macrophage crowding during in vitro culture is largely unstudied. Using a human induced pluripotent stem cell (iPSC)-derived macrophage model of tissue resident macrophages, we characterize how increasing macrophage culture density changes their morphology and phenotype before and after inflammatory stimulation. In particular, density drives changes in macrophage inflammatory cytokine and chemokine secretion in both resting and activated states. This density regulated inflammatory state is also evident in blood monocyte derived-macrophages, the human monocytic THP-1 immortalized cell line, and iPSC-derived microglia. Density-dependent changes appear to be driven by a transferable soluble factor, yet the precise mechanism remains unknown. Our findings highlight cell plating density as an important but frequently overlooked consideration of in vitro macrophage research relevant to a variety of fields ranging from basic macrophage cell biology to disease studies.